First Observations of Elves and Their Causative Very Strong Lightning Discharges in an Unusual Small‐Scale Continental Spring‐Time Thunderstorm. Issue 1 (29th December 2020) - Kolmašová, Ivana; Santolík, Ondřej; Kašpar, Petr; Popek, Martin; Pizzuti, Andrea; Spurný, Pavel; Borovička, Jiří; Mlynarczyk, Janusz; Manninen, Jyrki; Macotela, Edith L.; Zacharov, Petr; Lán, Radek; et al.
Abstract: We show for the first time that elves can be produced by an unusual small‐scale continental spring‐time thunderstorm. The storm occurred in Central Europe, covered a very small area of ∼50 × ∼30 km and lasted only for ∼4 h on April 2, 2017. The fraction of intense positive cloud‐to‐ground lightning strokes was unusually high, reaching 55%, with a mean peak current of 64 kA. The peak currents of return strokes (RS) associated with elves exceeded ∼300 kA. Elves and their causative RS have been observed with different optical and electromagnetic recordings. Signatures of ionospheric disturbances indicating the presence of elves were found in measurements of displacement currents, ionospheric reflections of sferics and man‐made narrow‐band transmissions. All these electromagnetic observations coincide with four optical detections of elves and strongly suggest the occurrence of two more elves later in the decaying phase of the storm. Surprisingly, the same electromagnetic measurements indicate that other strong strokes did not produce any elves. Our simulation results show that the formation of an elve is not only determined by the high‐peak current of their causative strokes but that it is also controlled by the conductivity of the lightning channels and velocity of the current wavefront. We hypothesize that because of a lower conductivity of RS lightning channels and/or slower current waves only very strong strokes with peak currents above ∼300 kA might have been capable to produce observable elves during this thunderstorm. Key Points: Observed elves were produced during a small‐scale continental spring‐time thunderstorm The fraction of intense positive cloud‐to ground lightning strokes reached 55% Only very strong strokes (> ∼300 kA) were capable to excite observable elves during this thunderstorm